Metaphysics as a Remedy for the «Total Hopelessness of the Philosophical Situation» in the 1920s (Martin Heidegger, Max Scheler) - Jaran, François (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In this paper, we show how the «metaphysical turn» that Heidegger’s path took shortly after the publication of Being and Time (1927) can be explained starting from the erroneous interpretation of that work as a contribution to philosophical anthropology. Presenting the first reviews and critiques, we approach the texts written at the end of the 1920s in which Heidegger reinterprets his fundamental ontology in terms of a non-anthropological «metaphysics of Dasein». We end this article by underlining the role that Max Scheler certainly played in this transitory «conversion» to metaphysics.
Keywords: Martin Heidegger; metaphysics of Dasein; Being and Time; philosophical anthropology; Max Scheler